Resistive sensor for tetradecane and H2S based on SnO2 nanoparticles - Kundu, Shubhranil; Sarkar, Mrittika; Shaji, Jyothis; Ghosh, Ruma (Sensors and actuators. A. Physical., 2025)
The development of sensors for the detection of vapor biomarkers is emerging as a promising alternative for disease diagnosis. However, these sensors are needed to be developed for the volatile organic compounds (VOC) which are more specific to the diseases and should be portable, cost-effective, and simple to use for them to be deployed redundantly and be taken home. This work focuses on developing a tin dioxide (SnO2) nanoparticles-based resistive sensor for tetradecane, which is a biomarker of lung cancer, and hydrogen sulphide (H2S), which is a biomarker of hepatocellular carcinoma. Nanostructured SnO2 was synthesized using a hydrothermal method. The morphology of SnO2 was ensured to be nanoparticles using a field emission scanning electron microscope and its crystal structure was confirmed to be tetragonal with a crystallite size of 17.16 nm using an X-ray diffractometer. Next, the SnO2 nanoparticle-based sensor was tested for 0.9–19 parts per million (ppm) of both tetradecane and H2S at 250°C, which was found to be the optimum operating temperature of the sensor for both the VOCs. The sensor response ranged from 1.08–31.5 % and 0.45–9.1 % for 0.9–19 ppm of tetradecane and H2S, respectively. The SnO2 nanoparticle was found to be highly selective for the target gases when tested with methanol, ethanol, acetone, and ammonia but the response of the sensor overlapped across different concentrations of the two target gases. Hence, a simple algorithm using response, response time, and recovery time was devised to predict the two target VOCs accurately. [Display omitted] •SnO2 nanoparticles were synthesized and used for sensing tetradecane and H2S.•SnO2 exhibited 1.08–31.5 % response for 0.9–19 ppm tetradecane at 250°C.•SnO2 exhibited 0.45–9.1 % response for 0.9–19 ppm and H2S at 250°C.•A simple algorithm to accurately predict the two gases was developed.